Expert consensus on diagnostic management specification and biomarker disclosure for subjective cognitive decline - Neurodegenerative Disease Special Committee, China Association for Promotion of Health Science and Technology (Chinese Journal of Contemporary Neurology and Neurosurgery)
The concept of subjective cognitive decline (SCD) is currently receiving much attention, as SCD has a high risk of transitioning to mild cognitive impairment (MCI) and dementia. The ATN biomarker diagnostic framework can accurately diagnose SCD as preclinical Alzheimer′s disease (AD), which is an important window for precise prevention and treatment of AD. Based on the present diagnostic paradigms of clinical diagnosis and biomarker diagnosis for SCD, it is important to have fine management during the diagnostic process and precise communication and support after diagnosis for SCD patients, including diagnostic management specification, interpretation and recommendation diagnostic of biomarker disclosure, patients health management, and possible treatment for specific underlying causes. Previous studies have shown heterogeneity between clinical research and practice, and many doctors still feel unfamiliar with the concept of SCD and lack a systematic understanding. SCD diagnosis can provide patients with a certain degree of certainty, but it may also bring uncertainty about the expected risk of disease, and there is an urgent need to provide guidance to clinical doctors. So far, there is still a lack of Chinese expert consensus on diagnostic management specification, biomarker disclosure, and patient management of SCD. Based on the systematic summary of the current domestic and international research on the SCD, the consensus is written and aimed to improve the diagnosis and treatment level of SCD, guide high⁃quality preclinical AD research and lay the foundation for further clinical translation.